Desempenho e espermatogênese de alevinos de tilápia alimentados com farelo ou farinha de semente de algodão - Salaro, Ana Lúcia; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP]; Vicentini, Carlos Alberto [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1999)
Este trabalho avaliou o efeito do farelo e da farinha de semente de algodão no ganho de peso e na atividade testicular de alevinos de tilápia-do-nilo (Oreochromis niloticus). Cento e cinqüenta alevinos com peso médio inicial de 1,26 g foram mantidos em aquários de 45 L, com renovação contínua d'água, e alimentados por 120 dias com dietas isoprotéicas (28% PB) e isocalóricas (4.030 kcal EB/kg de ração) contendo 0%, 2%, 4% e 6% de semente de algodão descorticada e moída, e 24% de farelo de algodão. Foi observado que os níveis avaliados interferem na atividade testicular, diminuindo a espermatogênese, embora não tenham comprometido de forma significativa o ganho de peso dos alevinos.

This experiment evaluated the effect of cottonseed meal or cottonseed flour on growth and testis activity of Nile tilapia fingerlings (Oreochromis niloticus). One hundred and fifty fingerlings with mean initial weight of 1.26 g were maintained in 45 L aquaria with continuous water supply. Fish were fed in isoproteic (28% CP) and isoenergetic (4,030 kcal CE/kg of ration) diets during 120 days. The experimental diets comprised a control diet, without cottonseed flour or meal, and diets containing 2%, 4% and 6% of cottonseed flour and 24% cottonseed meal. The results indicated that the use of seed flour or meal should be limited since at the tested levels they interferred with testis activity although they had not adversely affected the weight gain of fingerlings.
Performance and spermatogenesis of nile tilapia fingerlings fed with cottonseed meal or cottonseed flour
Keywords: ganho de peso; atividade testicular; gossipol; fator antinutricional; sistema reprodutor; Oreochromis niloticus; weight gain; testis activity; gossypol; antinutritional factor; reproductive system; Oreochromis niloticus